A QUALITATIVE STUDY ON DOMINANT FACTORS CAUSING FIRES IN MEDAN CITY - Suci Maghfirah; Fadhlan Al Hafizh Mrp; Rezky Aprillia; Salianto Salianto; Dwi Ajeng Ramadhani; Ahmad Fitra Naufal (HEARTY, 2026)
Fire is one of the most frequent urban disasters that causes significant losses, both materially and in terms of human casualties. Medan City, as a metropolitan area with high population density and complex economic activity, has a substantial risk of fire incidents. This study aims to identify the dominant factors that cause fires in Medan City using a qualitative approach. Data were collected through document analysis of official reports from the Medan City Fire services for the period 2023–2024 and in-depth interviews with nine firefighters who have direct experience in handling fire incidents. The results indicate that the most dominant cause of fire is electrical short circuits, accounting for more than 50% of cases in each semester. In addition, gas cylinder leaks, unsupervised use of stoves or furnaces, and open waste burning also contribute significantly to fire occurrences. Environmental factors such as the dry season and dense residential areas further increase the risk of fire spread. Although the Medan City government has implemented various awareness and training programs, public awareness regarding fire safety still needs to be improved. This study concludes that fires in Medan City are caused by a combination of technical, behavioral, and environmental factors. Therefore, effective prevention strategies must involve enhanced electrical safety supervision, public education, and consistent enforcement of safety regulations.